The Main Factor in the Management of Private Enterprise Effectiveness - Jaroenpornsagul, Narumon; Krongcheep, Siriporn; Ponsen, Kitsuchin (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Currently, the system of companies and organizations are also rapidly changing. Several businesses are highly competitive to produce work piece or even the quality of service. They have knowledge in production, creation, moral of the manufacturer. The quality of the raw materials is in accordance with the price standards. The satisfaction of the clients is an important to consider in running on business. Consumers who are satisfied with the products and service will become permanent customers because they have confidence in products and services. Therefore, private companies should have the strategies for effective administration. This article is based on a review of literature, research, theories, and related theories from various scholars. Moreover, to recognize about the management of various private organizations are relevant factors to effectively administration. This article will be useful for the administrator and involved in the future.